Application Development Design “How To Make Money Online” Using The Wartefall Method (Case Study : CV Satoeasa For Indonesia) - Agil Setyo Prasandi; Tikaridha Hardiani (Procedia of Engineering and Life Science, 2021)
CV Satoeasa is a organization engaged in training and consulting services in the context of empowering and developing business actors. Satoeasa is supported by personnel who have competency standards and experience in the fields of entrepreneurship and local economic development. CV Satoeasa Untuk Indonesia is committed to increasing entrepreneurial capacity and is passionate about realizing a growing and developing business. use of the application "How To Make Money Online" to increase competitiveness with other companies, improve the quality of service to customers because now customers have more options to browse applications, compare and analyze services and ratings before choosing an application to be installed on their phone device . For the development of the application "How To Make Money Online" CV Satoeasa For Indonesia plans to create a web-based application with the aim of making it easier for customers to access it without having to install their personal device first. This research uses the waterfall method. In the waterfall method there are several steps including requirements, design, implementation, verification and maintenance. This "How To Make Money Online" application is still based on Android, therefore the author intends to make a web-based "How To Make Money Online" application development design. The result of this research is an application development design. Application development is easier with the application design that will be developed. The conclusion is the "How To Make Money Online" application development design using HTML (HyperText Markup Language) programming. Before this application was developed, it was based on Android and after it was developed it became web-based. In this application there are several menus including the homepage, articles, contacts, about us and help. Provide solutions to CV Satoeasa Untuk Indonesia regarding the design of the application development "How To Make Money Online" using the waterfall method